Please anyone I’m desperate
![Please anyone Im desperate class=](https://us-static.z-dn.net/files/d12/75f11dbe0f83f2864bb89f8f8f8218e4.png)
Answer:
the answer is B) 12a+6b
Step-by-step explanation:
3+9=12 so 3a+9a=12a,
7-1=6 so 7b-(1)b=6b
Step-by-step explanation:
calm down ! just breathe.
these are totally simple additions and one also very simple subtraction to make.
you know that you can combine terms based on the same variable, right ?
3a + 9a = 12a
7b - b = 6b
the result is then
12a + 6b, so B is the right answer.
this bases already on the same principle of actual numbers.
2×3 + 5×3 = 7×3 because this is also
(2 + 5) × 3
or
6×5 + 6×3 = 6×8 because this is also
6 × (5 + 3)
or
7×8 - 4×8 = 3×8 because this is also
(7 - 4) × 8
and so on.